(3z(BFor Whom(3y (Band (3z(BUnder What Conditions(3y (BIs MSBI Effective? A Conceptual Replication With High School Students With Autisms - Sarah K. Cox; Jenny R. Root
Replications provide credibility by demonstrating under what conditions experimental findings can be repeated, the premise behind evidence-based practices. Replications in single-case research also investigate generalization of findings across groups. For groups with high variability, such as individuals with autism, assumptions of generalizability should be based on learners who are similar in critical ways. The purpose of this study was to use Coyne et al.'s framework for replication and the next generation guidelines for single-case research to extend understanding of (3z(Bfor whom(3y (Band (3z(Bunder what conditions(3y (Bmodified schema-based instruction (an established evidence-based practice for individuals with autism) is effective. In this distal conceptual replication of Root et al., contextual and instructional variables of theoretical and practical importance were intentionally manipulated or maintained and reported to model transparency and support replicability. Four high school students receiving special education under the Individuals With Disabilities Education Act category of autism were taught mathematical and social problem-solving behaviors within the context of percentage-of-change word problems. Researchers used modified schema-based instruction and augmented reality in a one-on-one setting and assessed generalization to purchasing in the food court of a mall biweekly. We frame our discussion around the recommendations for replication research from Coyne et al. and recommendations for single-case research from Ledford et al., concluding with suggestions for future replications that use single-case research designs.s